2022
DOI: 10.1136/jitc-2022-005187
|View full text |Cite
|
Sign up to set email alerts
|

GD2-targeting CAR-T cells enhanced by transgenic IL-15 expression are an effective and clinically feasible therapy for glioblastoma

Abstract: BackgroundAggressive primary brain tumors such as glioblastoma are uniquely challenging to treat. The intracranial location poses barriers to therapy, and the potential for severe toxicity. Effective treatments for primary brain tumors are limited, and 5-year survival rates remain poor. Immune checkpoint inhibitor therapy has transformed treatment of some other cancers but has yet to significantly benefit patients with glioblastoma. Early phase trials of chimeric antigen receptor (CAR) T-cell therapy in patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…Similar or more potent bystander killing effects may be observed by arming CAR-T cells with cytokines such as IL-15 (59,60) or IL-2(61), which may be safer than systematically administered cytokine therapy. It was estimated, for example, that under physiologic conditions in dense tissues such as lymph nodes, the cytokine IL-2, interacts over a characteristic length scale of 8-14 cell diameters (80-140 µm), which is determined by a balance between diffusion and consumption of cytokine (62).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similar or more potent bystander killing effects may be observed by arming CAR-T cells with cytokines such as IL-15 (59,60) or IL-2(61), which may be safer than systematically administered cytokine therapy. It was estimated, for example, that under physiologic conditions in dense tissues such as lymph nodes, the cytokine IL-2, interacts over a characteristic length scale of 8-14 cell diameters (80-140 µm), which is determined by a balance between diffusion and consumption of cytokine (62).…”
Section: Discussionmentioning
confidence: 90%
“…Our observations suggest that bystander killing mechanisms may enable CAR-T cells to target more tumor cells than would be predicted from the target antigen expression pattern, and thus may contribute to tumor destruction even in the presence of tumor heterogeneity. Similar or more potent bystander killing effects may be observed by arming CAR-T cells with cytokines such as IL-15(59,60) or IL-2(61), which may be safer than systematically administered cytokine therapy. It was estimated, for example, that under physiologic conditions in dense tissues such as lymph nodes, the cytokine IL-2, interacts over a characteristic length scale of 8-14 cell diameters (80-140 μm), which is determined by a balance between diffusion and consumption of cytokine(62).…”
Section: Discussionmentioning
confidence: 91%
“…It is a useful tactic to increase the release of proinflammatory cytokines to increase the activity of tumor cells. Preclinical studies on GBM have shown that co-expression of IL-15 [ 126 ], IL-12 [ 64 ], IL-18 [ 127 ], IL-23 [ 128 ], and IFNα2 [ 103 ] enhances the effect of CAR-T. However, excessive cytokine secretion can lead to CAR-T toxicity: CRS and ICANS.…”
Section: Car-t Cell Therapy In Gbmmentioning
confidence: 99%
“…As examples for γ-cytokines, T cells with a GD2-specific CAR were engineered to release IL7 ( 14 ) or IL15 ( 15 , 16 ), the latter CAR T cells are currently explored for the treatment of neuroblastoma (NCT03721068, NCT03294954). CD19-specific CAR T cells engineered to release IL7 showed improved killing and expansion in pre-clinical models, however, less persistence compared to IL15 engineered CAR T cells ( 17 ).…”
Section: Procedures To Deliver the Cytokine Signal To Car T Cellsmentioning
confidence: 99%
“…As examples for g-cytokines, T cells with a GD2-specific CAR were engineered to release IL7 (14) or IL15 (15,16), the latter CAR T cells are currently explored for the treatment of neuroblastoma (NCT03721068, NCT03294954). CD19-specific TABLE 1 Selected CAR T cell trials exploring the safety and efficacy of added cytokine or cytokine receptor ("signal-3").…”
Section: Cytokine Released By Engineered Car T Cells (Cytokine Truck)mentioning
confidence: 99%